(untitled) (MAUSAM, 2004)
Indian summer monsoon rainfall plays a major role in the country’s agricultural production and economy of the country. Earlier studies related to monsoon rainfall variations are based on monthly, seasonal or annual scale and concluded that the variations are within the statistical limits. In this paper, an attempt has been made to study the variability on a smaller period of the scale based on Nakshatras, which have an average period of 13-14 days. As a pilot study sub-divisions of Maharashtra and Goa have been selected. The basic statistical parameters of rainfall amount for different Nakshatras are discussed. The coefficients of variation during peak monsoon season are high and of the order of 40% - 80%. This means that total reliance of agricultural activities on Nakshatra based rainfall activity normally followed by Indian farmers is not a very good practice.